Effects of stocking density on productive performance, economic profit and muscle chemical composition of pacu (Piaractus mesopotamicus H) cultured in floating cages - Montenegro, Luciano Federico; Cunzolo, Sebastián Abel; Preussler, Cesar Adrian; Hennig, Herman Hernando; Descalzo, Adriana Maria; Perez, Carolina Daiana (Wiley, 2022)
The present 360-day study aimed to evaluate the productive performance, economic profit and meat quality of pacu cultured in floating cages at different stocking densities. A total of 2880 juvenile pacu, initial weight 50 ± 0.9 g, were reared in eight floating cages of 18.375 m3. Two stoking densities were used: high stocking density (HSD; 26 fish/m3) and low stocking density (LSD; 13 fish/m3). On days 0, 90, 180, 270 and 360, 100 fish per group were used to determine the growth performance, productive indices and total economic profit. The total economic profit was calculated by indices that include the fish price, feed conversion ratio and diet cost, among others. On day 360, the chemical composition and fatty acid profile of the muscle tissues were determined. The LSD group had higher final biomass and weight gain than the HSD group (p = 0.0001 and p < 0.0001 respectively), which was probably associated with the higher protein efficiency ratio obtained in the LSD group (p < 0.05). Additionally, the economic profit from LSD on day 360 was 1.2 times higher than that from HSD (p < 0.0001). More protein and lipid contents were obtained from LSD (p = 0.0035 and p < 0.0001 respectively) while more moisture was obtained from the HSD (p < 0.0001) group. In addition, more eicosapentaenoic (EPA) (p = 0.0013), docosapentaenoic (DPA) (p = 0.0001) and docosahexaenoic (DHA) (p = 0.0003) fatty acids were obtained from LSD. We concluded that when pacu are cultured in floating cages, 13 fish/m3 density produce fish with more weight and better muscle chemical composition, improving the economic profit and the nutritional quality.